2022
DOI: 10.1097/sle.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Is Laparoscopy Underutilized for Sigmoid Volvulus?

Abstract: Purpose: Minimally invasive surgery has become increasingly prevalent. However, the majority of colectomies for volvulus are still performed via an open technique. The purpose of this study is to determine whether there is a difference in outcomes between laparoscopic and open procedures for sigmoid volvulus. Materials and Methods:The American College of Surgeons National Surgical Quality Improvement Program and colectomytargeted procedure databases were queried from 2013 to 2018. Patients undergoing partial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Several approaches have been described: meso-sigmoidoplasty, open sigmoidopexy, endoscopic or laparoscopic, and elective sigmoidectomy, by median laparotomy or total laparoscopic or laparoscopic-assisted [2][3][4][5]. A systematic review and meta-analysis of the safety and efficacy of laparoscopic surgery in the management of sigmoid volvulus performed by Ndong A in 2022 including a total number of 30810 patients with 29874 cases of volvulus, showed that laparoscopic surgery was performed in only 7% of cases (N =2089) [6]. Several options are possible concerning this route: sigmoidectomy, sigmoidopexy, stoma inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been described: meso-sigmoidoplasty, open sigmoidopexy, endoscopic or laparoscopic, and elective sigmoidectomy, by median laparotomy or total laparoscopic or laparoscopic-assisted [2][3][4][5]. A systematic review and meta-analysis of the safety and efficacy of laparoscopic surgery in the management of sigmoid volvulus performed by Ndong A in 2022 including a total number of 30810 patients with 29874 cases of volvulus, showed that laparoscopic surgery was performed in only 7% of cases (N =2089) [6]. Several options are possible concerning this route: sigmoidectomy, sigmoidopexy, stoma inversion.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 , 8 , 21 In this field, laparoscopic procedure with natural orifice specimen extraction is the current option. 71 On the other hand, patients with indefinite diagnosis, gangrenous stool, or peritoneal irritation findings during the admission in addition to unsuccessful endoscopic decompression are treated with emergency surgery. If the sigmoid colon is viable, surgical decompression alone (mortality 0%-5%, morbidity 5%-15%, and recurrence 15%-55%) may be performed, but a recurrence-reducing procedure such as sigmoidopexy, mesopexy, or mesoplasty (mortality 1%-10%, morbidity 10%-25%, and recurrence 10%-20%), or preferably sigmoid colectomy (mortality 1%-10%, morbidity 15%-25%, and recurrence 0%-1%) may also be added.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…3 5 7 10 13 19 27 36 The mortality is 0 to 2%, the morbidity is 10 to 25%, and the recurrence is 0 to 1%. 1 3 5 10 19 24 26 36 42 43 In this field, the best innovation of the recent time is natural orifice specimen extraction with laparoscopic sigmoidectomy and primary anastomosis. 44 45 46…”
Section: Recurrence-preventive Managementmentioning
confidence: 99%
“…1E). 10,19,42,43 As an elective procedure, it is strongly recommended in well-conditioned and nonelderly patients to prevent SV recurrence. 3,5,7,10,13,19 Sigmoidectomy may be performed by open surgery or preferably laparoscopy, and following resection, stoma or preferably primary anastomosis is added.…”
Section: Recurrence-preventive Managementmentioning
confidence: 99%
See 1 more Smart Citation